Utilization of coffee pulp cellulose for bioetanol production through simultaneous saccarification and fermentation (SSF) with cellulose enzymes - Anshar Patria; Melly Novita (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2012)
Abstract. The bioetanol development from biomass bases on lignocellulose like pulp of coffee is one of alternative energy which has potential to be applied in Indonesia. Beside of raw material sources that are so many in our country, the process is also environmentally friendly. Conversion of coffee pulp becomes ethanol using Simultaneous Sacharification and Fermentation (SSF) technology by cellulase had been done on this research. Sacharification process or hydrolysis process, cellulase enzyme will break cellulose polymer becomes glucose. Then, glucose through fermentation is changed to ethanol by using yeast Saccharomyces cerevisiae. This study using Completely Randomized Design (CRD) with factorial pattern consisting of two factors. Factor I is the optimum pH (P) consists of three standards are: P1 = 4, P2 = 4.5, P3 = 5. Factor II is the incubation time (fermentation) (T) consisting of four standard that is T1 = 24 hours, T2 = 48 hours, T3 = 72 hours, and T4 = 96 hours. Pretreatment to break the lignin is done by soaking in 2% H2SO4 for 20 hours in the erlenmeyer. The analysis performed consists of the initial analysis and final analysis. Initial analysis consisted of analysis of water content, pH analysis, levels of cellulose and glucose levels, against the skin of the coffee pulp before the simultaneous saccharification and fermentation (SSF), whereas the final analysis included analysis of ethanol content, the analysis of cellulose and glucose from a solution of ethanol produced. The optimum pH treatment (P), incubation time (fermentation) (T) and interaction optimum pH and incubation time (fermentation) (PT) has very significant (P ≤ 0.01), on levels of ethanol produced. The highest levels of ethanol obtained by fermentation of 96 hours and the optimum pH 4.5 and 5. Ethanol content is obtained that is equal to 6% and 6.07%.